Distribuição inteligente de adubos químicos via GPS com tecnologia para pequenos produtores - Gómez, Pedro Fernando Martín (2013)
This thesis deals on the development an autonomous system, able to move within a culture accurately and effectively, being functional and economically viable in small cultures, which constitute the most percentage to agricultural production area in Colombia. A system capable to mapping the boundaries of culture it has develop with sub metric GPS in free signal without real time correction, and generate an innovative and proprietary methodology that integrates many different systems to a level pilot of one hectare. The GPS data are stored in a file and used for limits correction with software developed, using methods of interpolation and optimization with cubic splines, to make the distribution of culture and establishment the points of automatic positioning to the vehicle within the culture. With these coordinates, the trajectories are generate using A* algorithm to move between two points fulfilling the tasks of culture, interacting with a remote computer over wireless network Xbee. The result is a vehicle capable of dispensing liquid fertilizer with an error less than 3% by volume, with the possibility of moving in a culture following the trajectory generated by A* algorithm with error less than 10 cm, based on the embedded sensing in the vehicle and supervised by remote computer.